2009
DOI: 10.1093/intimm/dxp010
|View full text |Cite
|
Sign up to set email alerts
|

In contrast to anti-tumor activity, YT cell and primary NK cell cytotoxicity for Cryptococcus neoformans bypasses LFA-1

Abstract: NK cell cytotoxicity requires two positive signals for killing of tumors. Activation receptors induce polarization of the microtubule organization center and degranulation, while leukocyte function-associated antigen (LFA)-1 is required for conjugate formation and actin polymerization and under some circumstances may be sufficient for NK cell cytotoxicity. Although the receptor for direct killing of fungi is not known, CD18, the beta2 chain of LFA-1, binds components of the capsule and cell wall of the opportu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…Subsequently, the three cell types were incubated with YT cells to assess the protective role from overexpression of PI-9. It is worth noting that NK cells and the YT cell line undergo similar mechanisms of cytotoxicity (32), are stimulated by common surface Ags (33), and express similar surface markers (34). Therefore, both cell types are used interchangeably in the literature.…”
Section: Overexpression Of Pi-9 Protects Hpb-mscs From Killingmentioning
confidence: 99%
“…Subsequently, the three cell types were incubated with YT cells to assess the protective role from overexpression of PI-9. It is worth noting that NK cells and the YT cell line undergo similar mechanisms of cytotoxicity (32), are stimulated by common surface Ags (33), and express similar surface markers (34). Therefore, both cell types are used interchangeably in the literature.…”
Section: Overexpression Of Pi-9 Protects Hpb-mscs From Killingmentioning
confidence: 99%
“…In contrast, NK cell contact with C. neoformans is not intimate but is characterized by NK cell microvilli penetrating the fungal capsule and binding to the underlying cell wall of the fungus. Maximal binding of NK cells to C. neoformans does not occur until after 2 h and is independent of LFA-1, and inhibition of fungal growth is not detectable until 4 h following maximal binding (14,23,43,44,46). With these similarities and differences in mind, we wondered whether NK cell microbicidal activity with C. neoformans is influenced in response to C. neoformans as it is in response to other target types.…”
mentioning
confidence: 99%
“…To assess whether NK cells from HIV-infected patients were able to bind to C. neoformans , we labeled the NK cells with phycoerythrin (PE)-Cy5-conjugated anti-CD11a and then cocultured them with FITC-labeled C. neoformans over time. It is worth noting that direct NK cell anticryptococcal activity is preceded by LFA-1 (CD11a/CD18)-independent binding of NK cells (36). Conjugates were identified when red fluorescence (NK cell) and green fluorescence ( C. neoformans ) were detected in the same event by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…However, we considered the possibility that NK cells from HIV-infected patients failed to polarize perforin because they made contact but did not form a synapse with C. neoformans . To address this possibility, we examined LFA-1, which had been shown to accumulate at the NK cell-cryptococcal synapse (36). Images demonstrated that LFA-1 accumulates at the NK cell-cryptococcal synapse, in NK cells from both HIV-infected patients (Fig.…”
Section: Resultsmentioning
confidence: 99%